Phosphorylated silk fibroin matrix for methotrexate release - Volkov, Vadim (2015)
Silk-based matrix was produced for delivery of a model anticancer drug, methotrexate (MTX). The calculation of net charge of silk fibroin and MTX was performed to better understand the electrostatic interactions during matrix formation upon casting. Silk fibroin films were cast at pH 7.2 and pH 3.5. Protein kinase A was used to prepare phosphorylated silk fibroin. The phosphorylation content of matrix was controlled by mixing at specific ratios the phosphorylated and unphosphorylated solutions. In vitro release profiling data suggest that the observed interactions are mainly structural and not electrostatical. The release of MTX is facilitated by use of proteolytic enzymes and higher pHs. The elevated -sheet content and crystallinity of the acidified-cast fibroin solution seem not to favor drug retention. All the acquired data underline the prevalence of structural interactions over electrostatical interactions between methotrexate and silk fibroin.